Surpassing the natural limits of serological diagnostic tests - D. William Provance, Jr.; Andressa da Matta Durans; Guilherme Curty Lechuga; Evandro da Rocha Dias; Carlos Medicis Morel; Salvatore Giovanni De Simone (hLife)
Serological tests have an important and irreplaceable role in the diagnosis of infectious diseases, both for individual patients and society. They indirectly identify the causative pathogen through the capture of antibodies, which contrasts with the direct detection by antigen and molecular biology tests that are also limited to active infections. Within point-of-care platforms, serodiagnostic assays can support immediate decisions in patient care and contain the spread of disease as they do not require highly trained personnel or dedicated infrastructure. By employing serodiagnosis, health officials can proactively respond and eliminate emerging health risks. Larger sample numbers can be screened in other formats for surveillance as well as securing donated blood supplies. Furthermore, an assay can be designed to detect any immunoglobulin from IgM to IgG and its subclasses, to IgA and IgE. However, most serological assays employ natural proteins as the defining antibody-capturing reagent, which compromises their performance by limiting the two critical parameters of a serodiagnostic test: specificity and sensitivity. To surpass this natural limitation, we have repurposed the β-barrel of fluorescent proteins to receive epitope sequences that dependably produce high-performing designer immunological reagents. Consequently, serodiagnosis can be conducted more accurately at a lower cost.